2010
DOI: 10.1038/onc.2010.375
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling maintains chemoresistance in myeloid leukemic cells

Abstract: The development of resistance against chemotherapy remains one of the major challenges in the clinical management of leukemia. There is still limited insight into the molecular mechanisms that maintain the chemotherapy-resistant phenotype, despite the obvious clinical relevance that such knowledge would have. In this study, we show that the chemotherapy-resistant phenotype of myeloid leukemia cells correlates with activation of the Hedgehog (Hh) pathway, whereas in chemosensitive cells, such activation is less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 21 publications
7
106
0
1
Order By: Relevance
“…24 Moreover, constitutive activation of the Hh pathway maintains chemoresistance through increasing drug efflux of ABC transporters (ABCB1 and ABCG2), 25 and Gli-1 maintained multidrug-resistant phenotype of myeloid leukemia by ABCB1. 26 These findings are further supported by the observation that ABCB1 and ABCG2 promoter regions have the consensus sequence of Gli-binding site, and Gli-1 directly bound to the consensus GACCACCCA-like motif located in the promoter regions of ABCB1 and ABCG2 to regulate their transcription in B-cell lymphoma and ovarian cancer cells. 27,28 However, our results demonstrate that ABCC1 was highly expressed in Huh-7-DN and Huh-7-trans cells; in Figure 7 The effects of LDE225 and itraconazole on expression of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation.…”
Section: Discussionmentioning
confidence: 55%
“…24 Moreover, constitutive activation of the Hh pathway maintains chemoresistance through increasing drug efflux of ABC transporters (ABCB1 and ABCG2), 25 and Gli-1 maintained multidrug-resistant phenotype of myeloid leukemia by ABCB1. 26 These findings are further supported by the observation that ABCB1 and ABCG2 promoter regions have the consensus sequence of Gli-binding site, and Gli-1 directly bound to the consensus GACCACCCA-like motif located in the promoter regions of ABCB1 and ABCG2 to regulate their transcription in B-cell lymphoma and ovarian cancer cells. 27,28 However, our results demonstrate that ABCC1 was highly expressed in Huh-7-DN and Huh-7-trans cells; in Figure 7 The effects of LDE225 and itraconazole on expression of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation.…”
Section: Discussionmentioning
confidence: 55%
“…Hh signaling has an important role also in hematopoietic stem cell self-renewal and in maintenance of cancer stem cells in leukemia (10,13). Shh, Smo, and the Shh target genes Gli1 and Ptc are expressed in the myeloid line K562 (13,35).…”
Section: Modulation Of Hh Signaling Affects Doxorubicin Accumulation mentioning
confidence: 99%
“…For instance, Hh signaling plays a crucial role in controlling the self-renewal behavior of malignant mammary cells (8), glioma stem cells (9), myeloid leukemia cells (10), or cancer stem-like cells in gastric cancer (11). Moreover, many studies have reported a correlation between Hh signaling and treatment resistance of cancer cells (4,12,13). Indeed, activated Hh signaling upregulates the expression of the MDR transporters MDR1 (ABCB1 or P-glycoprotein) and BCRP (ABCG2); (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Сигнальный путь HH через транскрипционный фактор GLI1 способен влиять на экспрессию генов ABC переносчиков ABCG2, MDR1, MRP1 и генов MVP и MGMT, принимающих участие в формировании химиорезистентности [53,90,91]. Показано, что GLI1 влияет на экспрессию MGMT, связываясь с GLI1-связывающим сайтом в его промотере [92].…”
Section: влияние на процессы химиорезистентностиunclassified